2009
DOI: 10.1016/j.febslet.2009.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of p53 function by protein kinase C isoforms revealed by a yeast cell system

Abstract: Edited by Varda RotterKeywords: p53 Protein kinase C isoform Cell growth Cell cycle p53 phosphorylation Yeast a b s t r a c tThe complexity of the mammalian p53 pathway and protein kinase C (PKC) family has hampered the discrimination of the effect of PKC isoforms on p53 activity. Using yeasts co-expressing the human wild-type p53 and a mammalian PKC-a, -d, -e or -f, we showed a differential regulation of p53 activity and phosphorylation state by PKC isoforms. Whereas PKC-a reduced the p53-induced yeast growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…PKC␣ can phosphorylate the C-terminal region of p53 at Ser-376 and Ser-378 (16) and inhibit p53 in yeast (20), whereas PKC␣ overexpression promoted murine p53 transcriptional activity (17). The observed differences in the role of PKC␣ in p53 regulation could be a consequence of differences between the model systems used.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…PKC␣ can phosphorylate the C-terminal region of p53 at Ser-376 and Ser-378 (16) and inhibit p53 in yeast (20), whereas PKC␣ overexpression promoted murine p53 transcriptional activity (17). The observed differences in the role of PKC␣ in p53 regulation could be a consequence of differences between the model systems used.…”
Section: Discussionmentioning
confidence: 71%
“…2C). PKC␣ can phosphorylate p53 in vitro (16), although its effect upon p53 activity remains unclear (17,20). Importantly, under three-dimensional collagen conditions, M21 (␣v ϩ ) cells with stably knocked down PKC␣ exhibited a reduced p53 relocalisation with a greater proportion of p53 within the nucleus compared with control M21 cells stably expressing GFP knockdown sequences (Fig.…”
Section: Identification Of Integrin ␣V-and Three-dimensional Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors, which have been defined as regulators of p53 posttranslational modifications and activation, include Chk2 and ATM. 24,30,31 By using HCT116 Chk2 À / À cells and a specific inhibitor of ATM (KU55933), we could conclude that these factors did not contribute significantly to any of the 5-FU-induced p53 phosphorylation events analyzed. Still, in Chk2 À / À cells, processing of caspases-3 and -8 occurred at a slower rate compared with the parental cell line, implicating this factor in 5-FU-induced apoptosis by a yet unknown mechanism (Figure 6c).…”
Section: Dr5mentioning
confidence: 90%
“…Among kinase-dependent activity pathways acting on p53, only two are controlled by Ca 2 þ signaling. One of them involves serine/threonine kinase members included in a subgroup of the protein kinase C (PKC) family termed the classical group encompassing PKCs-a, -bI, -bII and -g. [24][25][26] The other one is facilitated by the ubiquitous Ca 2 þ -sensing protein CaM and occurs through activation of members contained in the superfamily of CaM-dependent kinases. [27][28][29] As a selective inhibitor of PKC (PKC412) did not attenuate p53 S15 phosphorylation in any of the concentrations tested, we concluded that this kinase did not contribute to the 5-FUinduced and Ca 2 þ -dependent events leading to p53 activity.…”
Section: Dr5mentioning
confidence: 99%